History of Nordic Computing 3 Third IFIP WG 9.7 Conference, HiNC 3, Stockholm, Sweden, October 18-20, 2010, Revised Selected Papers - Impagliazzo, John.; Lundin, Per.; Wangler, Benkt; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed post-proceedings of the Third IFIP WG 9.7 Conference on the History of Nordic Computing, HiNC3, held in Stockholm, Sweden, in October 2010. The 50 revised full papers presented together with a keynote address and a panel discussion were carefully reviewed and selected from numerous submissions. The papers focus on the application and use of ICT and ways in which technical progress affected the conditions of the development and use of ICT systems in the Nordic countries covering a period from around 1970 until the beginning of the 1990s. They are organized in the following topical sections: computerizing public sector industries; computerizing management and financial industries; computerizing art, media, and schools; users and systems development; the making of a Nordic computing industry; Nordic networking; Nordic software development; Nordic research in software and systems development; teaching at Nordic universities; and new historiographical approaches and methodological reflections.
Keywords: Computer science; Computer industry; Education; Computer Science; History of Computing; Computers and Society; The Computer Industry; The Computing Profession; Computers and Education; Personal Computing